Use of Saliva to Assess the Adherence to Treatment with Oral Hypoglycemic Agents in Patients with Type 2 Diabetes - de Faria Baltazar, Heloisa; Fonseca, Fernando Luiz A.; Castelo, Paula Midori; da Costa Aguiar Alves, Beatriz; Gascón, Thaís; da Veiga, Glaucia Luciano; Pereira, Edimar Cristiano (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: The diagnosis of Type 2 Diabetes Mellitus (T2DM) is made by demonstrating the hypoglycemic condition, which involves the determination of plasma glucose, and the follow-up of hypoglycemic treatment is performed by assessing the glycated hemoglobin (HbA1c) concentration. Aim: The aim of this study was to evaluate the saliva as an alternative sample in assessing the adherence to treatment with oral hypoglycemic agents in patients with Type 2 Diabetes. Methods: We selected 68 patients with T2DM, who were subjected to venous blood and saliva collection, in addition to answering a standardized questionnaire on adherence to hypoglycemic treatment. Laboratory tests performed on saliva, whole blood, serum or plasma included assessment of glycemia, urea, creatinine, uric acid, total cholesterol, HDL-cholesterol, LDL-cholesterol, VLDL-cholesterol, and glycated hemoglobin. Results: It was concluded that 82% of the patients adhered to hypoglycemic treatment based on glycated hemoglobin concentration (cut-off value of 7.0%). Comparing the groups that adhered to hypoglycemic treatment and those that did not adhere, statistical differences (P<0.05) were observed in the glucose, HDL-cholesterol, triglycerides, and insulin use (insulin therapy) parameters. Plasma glucose and urea serum concentration showed positive correlations when compared to saliva samples. Regarding the questionnaire, it was found that 35% of the patients presented positive screening for belief barriers and 83% positive score for recall barriers, and the positive screening correlated with glycated hemoglobin. Conclusion: Data have shown that it is possible to use saliva as an alternative sample to the laboratory assessment of hypoglycemic treatment adherence in T2DM patients.
Keywords: pharmacotherapeutic